2012
DOI: 10.1371/journal.pone.0030917
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Evidence That TRAF4 Is Required for Central Nervous System Myelin Homeostasis

Abstract: Tumor Necrosis Factor Receptor-Associated Factors (TRAFs) are major signal transducers for the TNF and interleukin-1/Toll-like receptor superfamilies. However, TRAF4 does not fit the paradigm of TRAF function in immune and inflammatory responses. Its physiological and molecular functions remain poorly understood. Behavorial analyses show that TRAF4-deficient mice (TRAF4-KO) exhibit altered locomotion coordination typical of ataxia. TRAF4-KO central nervous system (CNS) ultrastructure shows strong myelin pertur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 67 publications
1
33
0
Order By: Relevance
“…In contrast, TNFR2 signaling is predominantly neuroprotective as shown by the use of TNFR2-selective agonist that rescues neurons from oxidative stress-induced cell death [15]. Consistent with this, TNFR2-deficient mice exhibit delayed repair in models of remyelination [2] and targeted deletion of tumor necrosis factor receptor associate-factor 4 (TRAF4), a major signal transducer for TNF-α led to ultrastructure perturbation in myelin [6]. These data suggest that therapeutic strategies that antagonize TNFR1 to limit inflammation and augment TNFR2 signaling to enhance remyelination might provide effective treatments that both ameliorate disease and promote recovery in MS patients.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, TNFR2 signaling is predominantly neuroprotective as shown by the use of TNFR2-selective agonist that rescues neurons from oxidative stress-induced cell death [15]. Consistent with this, TNFR2-deficient mice exhibit delayed repair in models of remyelination [2] and targeted deletion of tumor necrosis factor receptor associate-factor 4 (TRAF4), a major signal transducer for TNF-α led to ultrastructure perturbation in myelin [6]. These data suggest that therapeutic strategies that antagonize TNFR1 to limit inflammation and augment TNFR2 signaling to enhance remyelination might provide effective treatments that both ameliorate disease and promote recovery in MS patients.…”
Section: Discussionmentioning
confidence: 99%
“…Within the resistant H/W strain, these findings (overexpression of Sod3 and reduced expression of Ero1l) align with the reduced carcinogenic effects of TCDD. Traf4 is a common oncogene (Camilleri-Broet et al, 2007), however overexpression has also been shown to be essential for homeostasis of CNS myelination (Blaise et al, 2012).…”
Section: Transcription Factor Binding Site Analysismentioning
confidence: 99%
“…Another gene within this region, TRAF4, encodes a family member of the tumor necrosis factor receptor-associated factors, which interacts with the neurotrophin receptor, p75 (NTR/NTSR1) and negatively regulates NTR induced cell death and NF-kappa B activation. TRAF4 is expressed in central nervous system neurons and in oligodendrocytes from early progenitors to mature myelinating cells (Blaise et al, 2012). TRAF4 has been shown to be involved in the subcellular localization of reactive oxygen species products in endothelial cells (Wu et al, 2005), in the maintenance of epithelial cell polarity and in the migration of dendritic cells.…”
mentioning
confidence: 99%
“…TRAF4 has been shown to be involved in the subcellular localization of reactive oxygen species products in endothelial cells (Wu et al, 2005), in the maintenance of epithelial cell polarity and in the migration of dendritic cells. In addition, TRAF4 plays a role in proper myelination, and TRAF4-deficient mice exhibit altered locomotion probably due to Purkinje cell loss in the cerebellum (Blaise et al, 2012). This makes TRAF4 an attractive candidate gene for movement disorders, including TS.…”
mentioning
confidence: 99%